2020
DOI: 10.3390/ijerph17176103
|View full text |Cite
|
Sign up to set email alerts
|

Maggot Therapy in Wound Healing: A Systematic Review

Abstract: Background: It is estimated that 2% of the population in developing countries suffer from a chronic wound, making it a hidden phenomenon that is increasing as populations age. The ease of access to maggot therapy has made it increasingly attractive for implementation. This study aimed to explore the effectiveness of maggot therapy as compared to hydrogel dressings in the healing of chronic wounds. Methods: An electronic literature search until October 2019 was performed using Medline, Embase, and Cumulative In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 25 publications
0
32
0
5
Order By: Relevance
“…The current treatment strategies for chronic wounds typically include application of standard and advanced wound dressings 1 and compression bandaging 2 . Ultrasound 3 , debridement 4 and skin substitutes 5 , 6 are more advanced therapeutic interventions, but the treatment of chronic wounds remains challenging and still requires orthogonal treatment strategies. Examples include physical methods, such as negative pressure wound therapy 7 and real-time sensing applications that can support clinical decision making (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The current treatment strategies for chronic wounds typically include application of standard and advanced wound dressings 1 and compression bandaging 2 . Ultrasound 3 , debridement 4 and skin substitutes 5 , 6 are more advanced therapeutic interventions, but the treatment of chronic wounds remains challenging and still requires orthogonal treatment strategies. Examples include physical methods, such as negative pressure wound therapy 7 and real-time sensing applications that can support clinical decision making (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as insects such as cockroaches possess an innate system and rely on this entirely instead of adaptive immunity, it is imperative to study these mechanisms as well as to examine the various antimicrobial peptides produced by these interesting species [ 88 ]. Nonetheless, it is also important to highlight that there are gaps in the understanding of the interaction between the microbiome and the host and the pathway of its metabolites, as well as how these metabolites may influence the microenvironment, and further mechanistic studies should be accomplished, as previously described [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two methods of application of maggots to wound bed described in the literature were free larvae and bagged larvae. 13 Theoretically, maggots need to be freely crawling to exert physical debridement effect. However, a recent randomised controlled trial conducted by Dehghan and colleagues to compare these two methods have shown similar efficacy of debridement 21 .…”
Section: Discussionmentioning
confidence: 99%
“…MDT is an alternative biological debridement option for patients who are not fit for surgery or for patients with chronic wound that have failed other options of treatment. 13 We report two patients with serious MDRO infection of the hand in which undergoing repeated debridement surgeries was not possible due to patients’ multiple medical comorbidities. Both patients were eventually successfully treated with three cycles of MDT followed by Negative Pressure Wound Therapy (NPWT).…”
Section: Introductionmentioning
confidence: 99%